PEMODELAN SISTEM PEMBANGKIT HYBRID ENERGI SOLAR DAN ANGIN - Harmini, Harmini; Nurhayati, Titik (Elektrika, 2018)
Hybrid energy system is to combine two energy sources that will provide power to the load. Sources of solar energy and wind energy will be used to generate power. In this research will be designed a model of hybrid system of solar energy and wind energy. The system is made equipped with energy storage systems in the form of batteries. Simulation or modeling using a circuit with components appropriate to the field application. Analysis of this system is the performance of hybrid generator characteristics based on load changes in the form of voltage, current and power values. The power generated by the PLTS is 3,000 Watts and the wind generator is 1,000 Watt with a resistive load of 4,000 Watt. Hybrid system generates a power of 2640 Watt so that the efficiency of hybrid system by 66%Keywords: Hybrid system, wind energy, solar energy